2023
DOI: 10.1128/spectrum.04027-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rhizospheric and Endophytic Bacterial Compositions between Netted and Oriental Melons

Abstract: The study of the differential structures and functions of rhizospheric and endophytic bacterial communities between netted melon and oriental melon treatments is investigated. Our findings make a significant contribution to the literature because they are the first step in coupling the study of rhizospheric and endophytic microbial community structure to reticulation formation in netted melon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
5
9
2
Order By: Relevance
“…Previous examination of bacterial communities on melons identified increased bacterial diversity on melons with netted rinds as compared to non-netted rinds [22], however our study found the opposite with non-netted melons consistently having higher alpha diversity compared to netted melons. Although we found that bacterial diversity of non-netted melon rind was higher than netted rinds in this study, such differences could be the result of major differences in melon cultivars examined between the studies, the multiple locations within this PLOS ONE study, or our examination over several growth seasons.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Previous examination of bacterial communities on melons identified increased bacterial diversity on melons with netted rinds as compared to non-netted rinds [22], however our study found the opposite with non-netted melons consistently having higher alpha diversity compared to netted melons. Although we found that bacterial diversity of non-netted melon rind was higher than netted rinds in this study, such differences could be the result of major differences in melon cultivars examined between the studies, the multiple locations within this PLOS ONE study, or our examination over several growth seasons.…”
Section: Discussioncontrasting
confidence: 93%
“…Both bacterial families are Gram-negative and members of the phylum Pseudomonadota, renamed from Proteobacteria. Interestingly, Xiao et al found Proteobacteria to be the highest in both netted and oriental non-netted melons, similar to our findings [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although we found that bacterial diversity of non-netted melon rind was higher than netted rinds in this study, such differences could be the result of major differences in melon cultivars examined between the studies, the multiple locations within this study, or our examination over several growth seasons. Although our results do agree with the results from Xiao et al, who also found that there was a difference among the communities based on the netting of the melons rather than the varieties [22], while we did not look specific at the impact that all the different cultivars in this study had on the bacterial diversity we did find that netting of the melons did play a role in the bacterial composition although not a major one.…”
Section: Discussionsupporting
confidence: 82%